2019
DOI: 10.1088/1367-2630/aaf824
|View full text |Cite
|
Sign up to set email alerts
|

Memory-efficient tracking of complex temporal and symbolic dynamics with quantum simulators

Abstract: Tracking the behaviour of stochastic systems is a crucial task in the statistical sciences. It has recently been shown that quantum models can faithfully simulate such processes whilst retaining less information about the past behaviour of the system than the optimal classical models. We extend these results to general temporal and symbolic dynamics. Our systematic protocol for quantum model construction relies only on an elementary description of the dynamics of the process. This circumvents restrictions on c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…In taking quantum memory and thermodynamical advantages in stochastic modelling to a more general medium, we open up a number of future research avenues, some paralleling developments in quantum implementations of predictive generators, some unique to the wider spectrum. For example, our results can be further extended to encompass input-output [37,38] and continuous-time processes [30,32,50,66,70,71] as well as inference protocols [24], and the trade-off between memory-and thermal-efficiency can be explored to determine the generator that best compromises the two -and whether classical and quantum implementations agree on which generator this should be. This latter direction will also require developments even in the purely classical setting: while the optimal predictive generators can be systematically found, this remains an open question across all generators in general.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In taking quantum memory and thermodynamical advantages in stochastic modelling to a more general medium, we open up a number of future research avenues, some paralleling developments in quantum implementations of predictive generators, some unique to the wider spectrum. For example, our results can be further extended to encompass input-output [37,38] and continuous-time processes [30,32,50,66,70,71] as well as inference protocols [24], and the trade-off between memory-and thermal-efficiency can be explored to determine the generator that best compromises the two -and whether classical and quantum implementations agree on which generator this should be. This latter direction will also require developments even in the purely classical setting: while the optimal predictive generators can be systematically found, this remains an open question across all generators in general.…”
Section: Discussionmentioning
confidence: 99%
“…The corresponding measures D µ and C µ are known as the topological and statistical complexity. Recently, a growing body of work has established that quantum implementations of ε-machines (with memory costs D q and C q ) can generally undercut this minimality [27][28][29][30][31][32][33][34]: D q ≤ D µ and C q ≤ C µ , with the compression advantage sometimes able to grow unboundedly large [30,32,46,[48][49][50]. The present state-of-the-art quantum implementations [33] are defined implicitly through a unitary interaction:…”
Section: Memory Compressionmentioning
confidence: 99%
See 1 more Smart Citation
“…less memory -and provide a systematic procedure for their design -using insights from quantum stochastic modelling [12][13][14][15][16][17][18][19][20]. The resulting agents can display extreme scaling advantages over provably minimal classical counterparts [21].…”
Section: Introductionmentioning
confidence: 99%
“…Further developments have shown that even when modelling classical data, the most efficient models are quantum mechanical [24][25][26][27][28][29][30][31]. This has led to a quantum analogue of the statistical complexity -the quantum statistical memory -with distinct qualitative and quantitative behaviour [27,29,[32][33][34][35][36][37] that demonstrates even better alignment with our intuitive notions of what is complex [32,38], and a greater degree of robustness [39].…”
mentioning
confidence: 99%